Energy Starvation Induces a Cell Cycle Arrest in Escherichia coli by Triggering Degradation of the DnaA Initiator Protein - Charbon, Godefroid; Mendoza-Chamizo, Belén; Campion, Christopher; Li, Xiaobo; Jensen, Peter Ruhdal; Frimodt-Møller, Jakob; Løbner-Olesen, Anders (Frontiers in Molecular Biosciences, 2021)
During steady state Escherichia coli growth, the amount and activity of the initiator protein, DnaA, control chromosome replication tightly so that initiation only takes place once per origin in each cell cycle and regardless of growth conditions. However, little is known about the mechanisms involved during transitions from one environmental condition to another or during starvation stress. ATP depletion is one of the consequences of long term carbon starvation. Here we show that DnaA is degraded in ATP depleted cells. A chromosome replication initiation block is apparent in such cells as no new rounds of DNA replication are initiated while already started replication events proceed to completion.